Preparation of highly luminescent and color tunable carbon nanodots under visible light excitation for in vitro and in vivo bio-imaging. Issue 22 (10th November 2015) - Zheng, Min; Liu, Shi; Li, Jing; Xie, Zhigang; Qu, Dan; Miao, Xiang; Jing, Xiabin; Sun, Zaicheng; Fan, Hongyou
Abstract: Abstract : Carbon nanodots (CDs) have generated enormous excitement because of their superiority in water solubility, chemical inertness, low toxicity, ease of functionalization and resistance to photobleaching. Here we report a facile thermal pyrolysis route to prepare CDs with high quantum yield (QY) using citric acid as the carbon source and ethylene diamine derivatives (EDAs) including triethylenetetramine (TETA), tetraethylenepentamine (TEPA) and polyene polyamine (PEPA) as the passivation agents. We find that the CDs prepared from EDAs, such as TETA, TEPA and PEPA, show relatively high photoluminescence (PL) QY (11.4, 10.6, and 9.8%, respectively) at λex of 465 nm. The cytotoxicity of the CDs has been investigated through in vitro and in vivo bio-imaging studies. The results indicate that these CDs possess low toxicity and good biocompatibility. The unique properties such as the high PL QY at large excitation wave length and the low toxicity of the resulting CDs make them promising fluorescent nanoprobes for applications in optical bio-imaging and biosensing.